The Role of Satisfaction in Mediating Compensation and Work and Environment against Employee Retention Pt. Senyum Media Utama Jember (International Journal of Scientific Research and Management (IJSRM), 2020)
Compensation is one form of efforts to reduce the high turnover of employees. Therefore, the presence of a good compensation, the employee will keep his job. And this is one form of motivation given the company’s employee retention. Not only compensation that can affect employee retention. The work environment also affect employee retention. Any organization or company seeking better working conditions and satisfactory, so that employees in the work can feel satisfied with the work he did. The low turn over to the PT. Senyum Media Utama Jember indicate high commitment of its employees, but still there are employees who do not survive or out of the company although the amount is very minimal, so it needs to be tested how the compensation, organizational commitment and the work environment influence on satisfaction and retention. The population in this study were employees of PT. Senyum Media Utama Jember as much as 150. The sample is observed is determined by purposive sampling method with the remaining number is 108. The analytical tool used is the analysis of SEM. Based on the analysis of the study results and discussion, it can be concluded that compensation, organizational commitment and the work environment influence on satisfaction and retention and satisfaction may mediate compensation, organizational commitment and work environment on employee retention. The observed sample is determined by purposive sampling method with the remaining number is 108. The analytical tool used is the analysis of SEM. Based on the analysis of the study results and discussion, it can be concluded that compensation, organizational commitment and the work environment influence on satisfaction and retention and satisfaction may mediate compensation, organizational commitment and work environment on employee retention. The observed sample is determined by purposive sampling method with the remaining number is 108. The analytical tool used is the analysis of SEM. Based on the analysis of the study results and discussion, it can be concluded that compensation, organizational commitment and the work environment influence on satisfaction and retention and satisfaction may mediate compensation, organizational commitment and work environment on employee retention. Keywords: compensation, organizational commitment, work environment, satisfaction and retention